If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 4 = 4(x + -3) Reorder the terms: 4 + y = 4(x + -3) Reorder the terms: 4 + y = 4(-3 + x) 4 + y = (-3 * 4 + x * 4) 4 + y = (-12 + 4x) Solving 4 + y = -12 + 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + y = -12 + -4 + 4x Combine like terms: 4 + -4 = 0 0 + y = -12 + -4 + 4x y = -12 + -4 + 4x Combine like terms: -12 + -4 = -16 y = -16 + 4x Simplifying y = -16 + 4x
| 8n+n=8 | | (2x+5y)(x^2+4xy-5y^2)= | | 10+4a^2=26 | | 15h-12h=15 | | 29028+3/100=1000 | | 2(2z-2)=3(z+4) | | 12=5x-2y | | 8(r+8)=24 | | 3x+7i=9+yi | | -7x+2x-6=4x | | -8+v=3v-v | | 3c+10=25 | | 3(7+x)=4-(5+2x) | | -5(5)-5y=25 | | 8.5*3=33.5 | | 156=-4-8b | | 8*63=8*n+8*3 | | 13(4c-5)=8c-4 | | Ax=1+4x | | v^2-8v=-12 | | -1+2n-3+4n=2-6n+6n | | 4x+2=8+x | | x^3-4x^2+2x-6=0 | | 33=9+4n | | 9=b/4+7 | | 15x^22+7x-2=0 | | 11y-4(3+3y)=3-3(4-y) | | 5=-8(5+3a)-3(-7-7a) | | -99=12(x+3)+6x | | y+5=2y+3 | | -3(p-4)+6(-1+7p)=-72 | | -6+9y=12 |